Psychosocial and mental health challenges faced by emerging adults living with HIV and support systems aiding their positive coping: a qualitative study from the Kenyan coast - Moses K. Nyongesa; Carophine Nasambu; Rachael Mapenzi; Hans M. Koot; Pim Cuijpers; Charles R. J. C. Newton; Amina Abubakar (BMC, 2022)
Abstract Background In sub-Saharan Africa, there is little data on the challenges faced by young people living with HIV transitioning into adult life. Adapting the socio-ecological framework, this qualitative study investigated the challenges faced by emerging adults living with HIV from a rural Kenyan setting. Additionally, the study explored support systems that aid positive coping among these young adults. Methods In April 2018, in-depth interviews were conducted with a convenience sample of 22 young adults living with HIV (12 females), 18-24 years old, from rural Kilifi, coast of Kenya. Data were analyzed thematically using NVIVO 11 software. Results Young adults living with HIV from this setting face various challenges at different levels of the social ecosystem. At the individual level, key challenges they reported included acceptance of HIV positive status, antiretroviral adherence, economic burden associated with access to healthcare, building an intimate relationship, mental health problems, and HIV status disclosure. At the family level, death of parents, poverty, and being unaccepted were the commonly mentioned challenges. At the community level, socialization difficulties and long waiting time at the HIV clinic were highlighted. HIV stigma and discrimination were frequently reported across the different levels. Economic independence, social support (from families, friends, organizations, healthcare providers and peer meetings), and reliance on spirituality aided positive coping among these young adults amidst the challenges of living with HIV. Conclusions In this rural setting, emerging adults living with HIV face various challenges at the individual, family, and community level, some of which are cross-cutting. Our findings underscore the need for designing multi-level youth-friendly interventions that can address modifiable challenges encountered by emerging adults living with HIV in this and similar settings. Such interventions should incorporate appropriate context-specific support structures that may help these young people smoothly transit into adult life.